Identification of initiation sites for heavy-strand and light-strand transcription in human mitochondrial DNA. - Montoya, J (1982)
The initiation sites for heavy (H) and light (L) strand transcription in HeLa cell mitochondrial DNA have been investigated by mapping experiments utilizing in vitro "capped" mitochondrial RNA molecules or nascent RNA chains. Mitochondrial poly(A)-containing RNA molecules were labeled at their 5' ends with [alpha-32P]GTP and guanylyltransferase ("capping" enzyme) and mapped on the mitochondrial genome by DNA transfer hybridization and S1 nuclease protection experiments. A mapping site for the capped 5' ends was found on the H strand very near to the 5' terminus of the 12S rRNA gene, and another site was found on the L strand very near to the 5' terminus of the 7S RNA coding sequence. In parallel experiments, the 5' ends of the nascent chains isolated from mitochondrial DNA transcription complexes were similarly mapped very near to the 5' termini of the 12S rRNA gene and of the 7S RNA coding sequence. The in vitro capped RNA molecules and the nascent chains thus presumably identify the same transcriptional initiation sites on the H strand and the L strand. The occurrence of a second possible initiation site for H-strand transcription 90-110 nucleotides upstream of that described above--i.e., 20-40 nucleotides upstream of the tRNAPhe gene--had been previously indicated by a mapping analysis of the nascent RNA chains and has been confirmed in the present work. The presence of two initiation sites for H-strand transcription can be correlated with other types of evidence that point to two different transcription events leading to the synthesis of a polycistronic molecule corresponding to the almost entire H strand and to the synthesis of the rRNA species.